Peningkatan Jiwa Kewirausahaan Mahasiswa Melalui Seminar Bisnis: Inovasi Bisnis Untuk Generasi Muda - wilda widiawati; Rahmad Rahmad; Riswan Riswan; Hidjrianto Hidjrianto; Agilfahreza Agilfahreza; Muh Rafly Suryatno (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This community service program aims to enhance the understanding, motivation, and readiness for enterepreneurship among students through a business seminar themed on innovation as a strategy to build competitive enterprises. The background of this activity stems from the low interest of students in engaging in entrepreneurial ventures, which is attibuted to limited knowledge, lack of access to information, and minimal practical experience. The implementation method employed a community education approach through material delivery by practitioners and academis, combined with training based on interactive discussions and case studies that encouraged participants to develop creative, adaptive and solution-oriented mindsets. The activity was attended by 45 students from various study programs. Evaluation results indicated a significant improvement in understanding the concept of business innovation from 37,8% to 86,7%, entrepreneurial interest from 52,4% to 92,0% and readiness to design business ideas from 28,9% to 78,4%. Qualitatively, participants reported increased self-confidence, understanding of digital marketing strategies, and insights into managing innovative business. Theses findings align with previous studies emphasizing the effectiveness of participatory approaches in entrepreneurship education. This program has made a tangible contribution to shaping a creative, innovative and competitive young generation, while simultaneously supporting econimic growth based on creativity.